2023
DOI: 10.1007/s00213-023-06333-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SSRIs on fear learning: a systematic review and meta-analysis

Abstract: Rationale Selective serotonin reuptake inhibitors (SSRIs) are considered first-line medication for anxiety-like disorders such as panic disorder, generalized anxiety disorder, and post-traumatic stress disorder. Fear learning plays an important role in the development and treatment of these disorders. Yet, the effect of SSRIs on fear learning are not well known. Objective We aimed to systematically review the effect of six clinically effective SSRIs on acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 207 publications
0
2
0
Order By: Relevance
“…In addition to empirically supported psychotherapies, evidence-based pharmacotherapies for PTSD, namely selective serotonin reuptake inhibitors (SSRIs; e.g., Lee et al, 2016; Stein et al, 2009), may also work by improving ER (especially in the context of trauma-related stimuli) through their impact on the serotonin (5-hydroxytryptamine) system (e.g., Lesch, 2010). Specifically, a recent meta-analysis including experimental studies in both human and animal samples found that SSRIs reduced contextual fear expression or generalization and improved extinction learning to cue (Heesbeen et al, 2023). The authors concluded that SSRIs may reduce contextual fear expression by decreasing activation in the bed nucleus of the stria terminalis, which is considered an extended component of the amygdala that is involved in processing unpredictable and sustained threat and that is often overactive in individuals with PTSD (e.g., Brinkmann et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to empirically supported psychotherapies, evidence-based pharmacotherapies for PTSD, namely selective serotonin reuptake inhibitors (SSRIs; e.g., Lee et al, 2016; Stein et al, 2009), may also work by improving ER (especially in the context of trauma-related stimuli) through their impact on the serotonin (5-hydroxytryptamine) system (e.g., Lesch, 2010). Specifically, a recent meta-analysis including experimental studies in both human and animal samples found that SSRIs reduced contextual fear expression or generalization and improved extinction learning to cue (Heesbeen et al, 2023). The authors concluded that SSRIs may reduce contextual fear expression by decreasing activation in the bed nucleus of the stria terminalis, which is considered an extended component of the amygdala that is involved in processing unpredictable and sustained threat and that is often overactive in individuals with PTSD (e.g., Brinkmann et al, 2017).…”
mentioning
confidence: 99%
“…The authors concluded that SSRIs may reduce contextual fear expression by decreasing activation in the bed nucleus of the stria terminalis, which is considered an extended component of the amygdala that is involved in processing unpredictable and sustained threat and that is often overactive in individuals with PTSD (e.g., Brinkmann et al, 2017). Further, SSRIs may enhance extinction learning by reducing hyperresponsivity of the amygdala (Heesbeen et al, 2023).…”
mentioning
confidence: 99%